Development of Intercultural Competency on Islamic Education Materials at the State of East Kalimantan High School - Khojir, Khojir; Aini, Amalia Nur; Setiawan, Agus (IAIN Samarinda, 2021)
Islamic education and multiculturalism are connected each other where the content of multiculturalism in national scale includes religious character as one of the core components, whereas in Islamic education relies on commands and prohibitions regarding multiculturalism stated in Alqur’an. Therefore, since intercultural competence and religious character development of students are considered to be important and become one of fundamental objectives existed in national curriculum of 2013 in Indonesia, this research is aimed at conducting Research and Development (R & D) related to developing Islamic Religious course or what so called by Pendidikan Agama Islam (PAI) in Indonesian context in high schools in East Kalimantan, Indonesia. In terms of data collection, the data gained from observation, interview, questionnaire, and validation techniques. Moreover, five stages of ADDIE model were employed in conducting the development research of PAI materials which includes Analisis, Design, Implementation, and Evaluation stages. As a result, findings showed that material design of PAI teaching is feasible and effective to be used in PAI teaching and learning due to good criteria gained from the validation result from material expert and excellent category from media expert. Students’ responses towards the implementation of product design of PAI teaching materials showed good to excellent result towards all aspect assessment. Highlighting points regarding novelty and pedagogical implication are discussed further in this research.